Decision-making in clinical practice: "4E" evidence-based framework proposal - Alva-Diaz, Carlos (2022)
background: Human decisions are partially rational. In medicine, critical scenarios make decide-making (DM) difficult. In this review, we propose the "4E" approach to improve the DM of interventions. The "4E" approach includes decisions: "effectual" when interventions have been tested in controlled settings, "effective" when interventions have been tested in uncontrolled or pragmatic clinical settings, "efficient" when the benefits of a new intervention are evaluated by its costs, and decisions that promote "equity" when these interventions are recommended according to the needs of the patient, avoiding barriers. Using this approach could improve DM in clinical practice, but it is not enough to guarantee its incorporation and use. It is also essential to promote the organizational, institutional, and political dynamics of health systems that promote evidence's critical use to make decisions.